Collaboration Partnership Model Between Sugarcane Farmers And PG Madukismo - Derik Rizki Purnama; Dimas Deworo Puruhito; Resna Trimerani (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2024)
Purpose: This study aims to identify the partnership collaboration model at PG Madukismo, detailing the rights and obligations of both parties, and to understand the benefits and challenges within the partnership. Methodology: The research was conducted at PG Madukismo in Padokan Tirtonirmolo Kasihan, Bantul Regency. A qualitative case study approach was employed, with a sample size of 30 partner farmers from the Western and Eastern regions. Data were analyzed descriptively. Results and Findings: The partnership collaboration models at PG Madukismo include the Independent People's Sugarcane (TRM) model and the People's Sugarcane Partnership (KMT) model, each with specific rights and obligations. The benefits of the partnership include increased sugarcane productivity, guarantees of quantity, quality, and continuity, and reduced risks in sugarcane farming. However, challenges include insufficient support from PG Madukismo to enhance the welfare of partner sugarcane farmers. Novelty and Originality: This study provides a detailed examination of the partnership models and highlights specific benefits and challenges faced by the partner farmers, contributing to the understanding of agricultural partnerships. Conclusions: The partnership models at PG Madukismo offer significant benefits but are hindered by inadequate support from PG Madukismo. Addressing these challenges could enhance the effectiveness of such partnerships. Type of Paper: Empirical Research Article